The Concept of Divine Justice in The Quran Thematic Analysis of Al Adl - Ayub, Satry; M. Yusuf; Mardan, Mardan (PT. Hafasy Dwi Nawasena, 2026)
The Quran, as the holy scripture of the Islamic community, not only provides spiritual guidance but also emphasises the importance of justice in various aspects of life. The research method employed in this study is a qualitative approach with thematic analysis. Several verses of the Quran elucidate the concept of justice, one of which is found in Surah An-Nisa, verse 129, which explains that although a husband may have multiple wives, absolute justice among them is challenging to achieve. The intrinsic nature of Allah as the Most Just reflects that His justice is not influenced by external factors or specific conditions. The active attributes of divine justice focus on Allah's actions and decisions in governing human life. In the context of social relations, justice encompasses equal treatment of all individuals regardless of their background, social status, or wealth. The divine justice taught in the Quran serves not only as a moral guideline but also as a foundation for the formulation of public policies and improved social systems. It is essential for Muslims to continuously explore and comprehend the principles of justice in the Quran and to apply them in their daily lives.